Economic Growth, Investment, and Education Influences on Income Inequality in Yogyakarta - Trisnaningrum, Ninda Ayu Wigi; Primandhana, Wiwin Priana (Gorontalo Development Review, 2025)
This study examined the factors influencing income inequality in the Special Region of Yogyakarta, specifically looking at economic growth, investment, and the average years of schooling. The results indicate that while economic growth has no significant effect, investment plays a crucial role in reducing income inequality. Interestingly, the average years of schooling was found to be positively and significantly correlated with income inequality, suggesting that higher education levels may be widening the income inequality.